2022
DOI: 10.1016/j.jsxm.2022.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Erectile Dysfunction and Altered Contribution of KCa1.1 and KCa2.3 Channels in the Penile Tissue of Type-2 Diabetic db/db Mice

Abstract: Background Activation of endothelial small conductance calcium-activated K+ channels (KCa2.3) and intermediate conductance calcium-activated K+ channels (KCa3.1) leads to vascular relaxation. We found endothelial KCa2.3 down-regulation in the corpus cavernosum diminishes erectile function. Aim We hypothesized that in type-2 diabetic mice, the function of KCa2.3 and KCa1.1 channels is impaired in erectile tissue. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…To further investigate the effects of IP2015 in a simple model of erectile dysfunction, before dissecting its underlying pharmacology in vivo, we assessed its effects in db/db mice, a model of Type 2 diabetes. The db/db mice have decreased erectile function compared with normal C57BL/6 mice and heterozygous db/+ control mice (Comerma‐Steffensen et al, 2022). Infusion of IP2015 (1 mg·kg −1 ) in diabetic db/db mice significantly increased the frequency, duration and magnitude of erectile responses (Figure 2h–j).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To further investigate the effects of IP2015 in a simple model of erectile dysfunction, before dissecting its underlying pharmacology in vivo, we assessed its effects in db/db mice, a model of Type 2 diabetes. The db/db mice have decreased erectile function compared with normal C57BL/6 mice and heterozygous db/+ control mice (Comerma‐Steffensen et al, 2022). Infusion of IP2015 (1 mg·kg −1 ) in diabetic db/db mice significantly increased the frequency, duration and magnitude of erectile responses (Figure 2h–j).…”
Section: Resultsmentioning
confidence: 99%
“…Erectile dysfunction occurs in 46% of men with Type 2 diabetes (Gratzke et al, 2010). Type 2 diabetic db/db mice have the most severe erectile dysfunction compared with heterozygous control and normal C57BL/6 mice (Comerma‐Steffensen et al, 2022). Our findings that IP2015 could induce erectile responses reflected by increases in intracavernosal pressure and duration in diabetic mice suggest that IP2015 may improve erectile function in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Due to abnormalities in leptin, the hormone that causes a feeling of fullness, Zucker Fatty rats, Otsuka Long-Evans Tokushima Fatty (OLETF) rats, db/db mice, and nonobese type 2 diabetes model Gotoh-Kakizaki (GK) rats were used in sexual function studies. [42][43][44][45] It has been reported that these animals are affected by ED.…”
Section: T Ypic Al Patholog Ic Al Ed Model Animal Smentioning
confidence: 97%
“…Additionally, animal models of type 2 diabetes have been created by rearing animals on a diet containing high amounts of carbohydrates and lipids 41 . Due to abnormalities in leptin, the hormone that causes a feeling of fullness, Zucker Fatty rats, Otsuka Long‐Evans Tokushima Fatty (OLETF) rats, db/db mice, and nonobese type 2 diabetes model Gotoh‐Kakizaki (GK) rats were used in sexual function studies 42–45 . It has been reported that these animals are affected by ED.…”
Section: Typical Pathological Ed Model Animalsmentioning
confidence: 99%